2018
DOI: 10.3389/fmicb.2018.02139
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Natural Antimicrobial Can Reduce the in vitro and in vivo Pathogenicity of T6SS Positive Campylobacter jejuni and Campylobacter coli Chicken Isolates

Abstract: Human campylobacteriosis is considered one of the most common foodborne diseases worldwide with poultry identified as the main source of infection accounting for 50–80% of human cases. Highly virulent Campylobacter spp., positive for the Type VI secretion system (T6SS), which have an increased ability to adhere to and invade the host gastrointestinal epithelium are highly prevalent in poultry. Multidrug resistant strains of bacteria are rapidly evolving and therefore, new antimicrobials to supplement animal fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 58 publications
0
46
0
1
Order By: Relevance
“…Infecting human gastrointestinal cells lines (HCT-8) with Campylobacter spp. highlighted that the T6SS system is involved via the downregulation of hcp gene expression in the reduction of the bacterium's ability to adhere and infect in vitro [13]. The same study also showed that the effect was extrapolated in vivo when chicken broilers where challenged with Campylobacter spp.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Infecting human gastrointestinal cells lines (HCT-8) with Campylobacter spp. highlighted that the T6SS system is involved via the downregulation of hcp gene expression in the reduction of the bacterium's ability to adhere and infect in vitro [13]. The same study also showed that the effect was extrapolated in vivo when chicken broilers where challenged with Campylobacter spp.…”
Section: Introductionmentioning
confidence: 80%
“…According to our results, such mixtures can be used efficiently in both fresh and marine water environments, as we have observed similar results in low and high salt conditions. Similar antimicrobial mixtures have been previously used to prevent the bacterial infection of epithelial cells, both in vitro and in vivo [13], through the inactivation of virulence factors. The link between T6SS inactivation and decreased virulence has been previously shown, as it has been indicated that its presence enhances the adhesion to cultured cell monolayers [43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations